2020
DOI: 10.3390/molecules25133060
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids and Mitochondria: Activation of Cytoprotective Pathways?

Abstract: A large number of diverse mechanisms that lead to cytoprotection have been described to date. Perhaps, not surprisingly, the role of mitochondria in these phenomena is notable. In addition to being metabolic centers, due to their role in cell catabolism, ATP synthesis, and biosynthesis these organelles are triggers and/or end-effectors of a large number of signaling pathways. Their role in the regulation of the intrinsic apoptotic pathway, calcium homeostasis, and reactive oxygen species signaling is w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(52 citation statements)
references
References 206 publications
(232 reference statements)
4
48
0
Order By: Relevance
“…Synthesis of ATP by catabolism of carbon-rich sources via oxidative phosphorylation is one of the major roles of mitochondria. The integrity of the inner mitochondrial membrane is very much essential to normal physiological and biophysical functioning [ 93 ]. Mitochondrial damage during oxidative insult like the accumulation of cardiotoxins or due to ischemia/reperfusion is considered a key event leading to cardiomyocytes dysfunction and apoptosis [ 94 ].…”
Section: Cardioprotective Potential Of Dietary Flavonoidsmentioning
confidence: 99%
“…Synthesis of ATP by catabolism of carbon-rich sources via oxidative phosphorylation is one of the major roles of mitochondria. The integrity of the inner mitochondrial membrane is very much essential to normal physiological and biophysical functioning [ 93 ]. Mitochondrial damage during oxidative insult like the accumulation of cardiotoxins or due to ischemia/reperfusion is considered a key event leading to cardiomyocytes dysfunction and apoptosis [ 94 ].…”
Section: Cardioprotective Potential Of Dietary Flavonoidsmentioning
confidence: 99%
“…Fisetin (3,7,3′,4′-tetrahydroxy flavone) is a flavonol that is ubiquitous in trees, fruits, and vegetables [ 16 , 17 ]. It has been reported that fisetin has numerous pharmacological properties, including anticancer [ 18 ], antioxidative [ 19 ], antimelanogenic [ 20 ], and anti-inflammatory [ 21 ] activities.…”
Section: Introductionmentioning
confidence: 99%
“…Such bioactivities were mediated through the interference with the inflammation and apoptosis processes [ 10 , 27 , 30 , 31 , 32 ]. Moreover, phenolic compounds and flavonoids in particular are known for their anti-inflammatory activity [ 87 , 88 ] besides which they have the ability to reduce apoptosis in normal cells triggered by various stimuli [ 89 ]. Therefore, the isolated compounds as well as the other compounds which we identified them previously in C. annua extract (mainly phenolics) [ 29 ] were scrutinized using protein-ligand docking to predict their binding interactions towards the caspase-3 (PDB:6 CKZ) and IFN-γ (PDB: 2R3Z) proteins obtained from the Protein Data Bank (MOE ® -2019) in a trial to link these phytochemicals with the experimental results.…”
Section: Resultsmentioning
confidence: 99%